Governing Illegal Settlements: Housing Policy in Singapore and Australia - Handayani, I Gusti Ayu Ketut Rachmi; Ehsonov, Jasurbek Rustamovich (Lembaga Contrarius Indonesia, 2024)
The increase in population has an impact on the proliferation of illegal settlements. This study determines and analyzes housing policies and administrative law enforcement about illegal settlements. The study uses normative legal research, which compares legal issues in two countries, Singapore and Australia. This research is descriptive, using both statute and conceptual approaches. The concept of administrative law enforcement and protecting citizens' fundamental rights are used as the basis for our analysis, combining it with legal system theory and administrative law enforcement. The research results show that, in substance, Singapore has a housing policy through Housing & Development Board, which is carried out on a massive scale and is quite successful in dealing with illegal settlements in urban areas about the size of the country's territory. Structurally, government institutions carry out administrative law enforcement through warnings and demolitions. Meanwhile, Australia has not been entirely successful, even though collaboration has been carried out between governments through Australia for Affordable Housing, the private sector, and housing communities. Australia enforces the law by issuing orders to stop using unauthorized buildings and imposing financial sanctions. Affordable and fair housing policies that the enforcement of administrative law can accompany are more effective in reducing illegal settlements than relying solely on the enforcement of administrative law alone or even criminal law. According to a culture of legal awareness, settlers who face various economic and social pressures are more difficult to discipline.